Interaction of germanium with platinum group metals in lateral diffusion couples - Habanyama, Adrian (Department of Physics, 2024)
Existing materials and technologies in the semiconductor industry are approaching their physical limits as device sizes decrease significantly below 100 nm. The challenges of achieving the required lateral abruptness of semiconductor junctions and low junction leakage as well as low contact resistance require a careful rebuilding of the fundamental physics and materials platform on which to base a reliable manufacturing capability. As feature size continues to decrease, interconnects will also pose increasingly difficult challenges in terms of physics and materials. The study of lateral diffusion couples is particularly well suited for dealing with the above concerns. This thesis looks at metal-germanium systems of the Platinum Group Metals (PG Ms). It is of particular relevance to study possible applications of PG Ms in South Africa, the country being one of the major producers of these metals in the world today. The diffusion lengths in standard thin-film couples range from a few angstroms to several thousand angstroms. In lateral diffusion couples, phase formation could extend to lengths of around 100 µm. Solid-state interactions in both thin-film and bulk diffusion couples can therefore be investigated using lateral diffusion couples. In particular the transition between the two types of interactions can be studied.